Determinants of successful opioid deprescribing: Insights from French pain physicians—A qualitative study. - Nizet, Pierre; Deme, Laure; Evin, Adrien; Kuhn, Emmanuelle; Nizard, Julien; Victorri Vigneau, Caroline; Huon, Jean‐François (Pain Practice, 2025)
Background: Long‐term use of opioids does not result in significant clinical improvement and has shown more adverse than beneficial effects in chronic pain conditions. When opioids cause more adverse effects than benefits for the patient, it may be necessary to initiate a process of deprescribing. Aim: To explore the perceptions of French pain physicians regarding the process of opioid deprescribing in patients experiencing chronic non‐cancer and to generate an understanding of the barriers and levers to the deprescribing process. Methods: We conducted a multicentric observational study with qualitative approach. Individual semi‐structured interviews exploring pain physicians' perceptions, beliefs, and representations to assess the determinants of opioid deprescribing with an interview guide were used. After checking the transcripts, an inductive and independent thematic analysis of the interviews was to extract meaningful themes from the dataset. Results: Twelve pain physicians were interviewed. The main obstacles to deprescribing revolved around patient‐specific attributes, characteristics of the opioids themselves, and limitations within the current healthcare system, that hinder optimal patient management. Conversely, patient motivation and education, recourse to hospitalization in a Pain Department with multidisciplinary care, follow‐up by the general practitioner, and training and information dissemination among patients and clinicians emerged as facilitative elements for opioid deprescribing. Conclusion: This study underscores the needs to improve the training of healthcare professionals, the effective communication of pertinent information to patients, and the establishment of a therapeutic partnership with the patient. It is therefore essential to carry out the deprescribing process in a collaborative and interprofessional manner, encompassing both pharmaceutical and non‐pharmaceutical strategies.